The weakest link - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
The real strength of this book, pithy enough for a UN author, lies in its recognition of the link between technical cooperation (TC) and national capacity building.